The Nutritive Value of Zornia glochidiata as a Non-conventional Feedstuff in Rabbit in Sokoto, Nigeria - Ogunsan, E.A.; Dogo, G.I.; Aliero, B.L.; Hassan, W.A.; Tambuwal, F.M.; Ogo, N.I.; Jatau, J. (Pakistan Journal of Nutrition, 2011)
An experiment was conducted to determine the effect of including Zornia glochidiata (ZG) in the diet of rabbit at 0 (control), 10, 20 and 30%. The results showed that increasing the level of supplementation of ZG beyond 10% decreased feed intake and subsequently live weight gain. Dry matter digestibility also followed a similar trend. Least cost of feed per kilogram live weight gain occurred at the 10% inclusion level of ZG. Although blood parameters differed significantly between treatments, they were mostly within acceptable physiological limits, suggesting no adverse effects in feeding ZG to the animals.